Training of simple fire installation for security guard at Samarinda State Polytechnic - Sudirman Sudirman; Hasan Basri (Universitas Muhammadiyah Magelang, 2021)
The Samarinda State Polytechnic has a hydrant that does not work, because the installation is damaged and is 35 years old. Currently, a simple fire fighting water installation has been made at three points with a length of 257 meters for 16 buildings, which utilizes lake water inside the Samarinda State Polytechnic campus. Therefore, this service activity is intended to provide skills for security guard in the Samarinda State Polytechnic regarding the use of hydrants. The specifications of the equipment used are portable centrifugal pumps with a maximum capacity of 700 liters/minute, a horizontal reach length of 40 meters, a vertical height of 12 meters and a pump pressure of ±5 bar. The results of this activity revealed that all security guard at the Samarinda State Polytechnic were able to operate a simple fire extinguisher installation. In addition, security personnel also have the ability to maintain a fire pump engine.